1997
DOI: 10.1111/j.1432-1033.1997.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression Studies on the ba3 Quinol Oxidase from Paracoccus Denitrificans A bb3 Variant is Enzymatically Inactive

Abstract: Expression of the quinol oxidase from Paracoccus denitrijicans has been examined using a polyclonal antibody directed against subunit I1 and a promoter probe vector carrying the promoter region of the qox operon. Under aerobic conditions nitrate and nitrite act as specific inducers of the expression. To obtain an enzymatically competent quinol oxidase complex, an intact ctaB gene is required, which constitutes part of the eta operon coding for the aa, cytochrome c oxidase of P: denitrificans. Deletion of ctaB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 36 publications
1
30
1
Order By: Relevance
“…In this study we address the question of heme composition of the E. coli oxidase when expressed in a P. denitrificans host, and show that the purified enzyme exhibits a ba 3 heme composition. In contrast to the previously described non‐functional quinol oxidase species with a b ‐type heme in the binuclear center [3, 4, 9, 10]this enzyme retains its electron transfer competence at wild‐type level.…”
Section: Introductioncontrasting
confidence: 74%
“…In this study we address the question of heme composition of the E. coli oxidase when expressed in a P. denitrificans host, and show that the purified enzyme exhibits a ba 3 heme composition. In contrast to the previously described non‐functional quinol oxidase species with a b ‐type heme in the binuclear center [3, 4, 9, 10]this enzyme retains its electron transfer competence at wild‐type level.…”
Section: Introductioncontrasting
confidence: 74%
“…Many reports have suggested that the promiscuous assembly of terminal oxidases may be a general phenomenon in bacteria, promoted by different culture conditions or as a consequence of specific mutations (2)(3)(4)(5)(6)(7)(8)(9)(10). In most cases, hemes O and A replace each other in the high spin site of the binuclear center, producing functional enzymes with somewhat different kinetic properties (2,4,18).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the substitution of heme O by heme B in the binuclear O 2 -reducing site in E. coli cyoE-deleted strains (cyoE encodes for farnesyl transferase that converts heme B to heme O) results in an inactive cytochrome bb 3 enzyme (10). Similarly Zikermann et al (7) reported that in Paracoccus denitrificans ctaB-deleted strains (the ctaB gene is an orthologue of cyoE), a bb 3 variant of bo 3 oxidase is enzymatically inactive. Examples of heme substitutions in the high spin heme site producing functional enzymes have been reported in several bacterial species; for example a novel b(o/a) 3 cytochrome c oxidase was purified from Bacillus stearothermophilus K17 mutants defective in caa 3 -type oxidase (8).…”
mentioning
confidence: 89%
“…For example, a bb 3 variant of ba 3 -QOX from Paracoccus denitrificans (although enzymatically inactive) has been described (73) in which heme B substitutes for heme A in the binuclear center as a result of impaired heme A biosynthesis. It is thus possible that the novel B. subtilis oxidase corresponds to the CydAB polypeptides containing three hemes B: one low spin (b 558 ) and two high spin (b 595 and bЈ).…”
Section: A Novel Oxidase Of Bbј Type In B Subtilis Strain 168 -Thismentioning
confidence: 99%